Has guideline development gone astray? No. (29th January 2010) - Gibbons, Raymond J; Antman, Elliott M; Smith, Sidney C
Abstract : The move to evidence based medicine has led to a proliferation of guidelines. R Grol (doi: 10.1136/bmj.c343 ) is concerned that many are of poor quality, but Raymond Gibbons and colleagues argue that guidelines are important for improving health